Nobel Prize Level Scientific Discoveries of a Heir of Zaporizhian Cossacks - Motsnyi, F. V. (Statistics of Ukraine, 2020)
In this work, three fundamental discoveries of the Ukraine-born Prof. George A. Gamow are presented from a single scientific and methodological point of view. Each of them is truly worth of the Nobel Prize – the most prestigious recognition of achievements of a scientist. We trace the emergence of G. Gamow as one of the most outstanding scientists of the twentieth century – encyclopaedist, theoretical physicist by heart, astrophysicist and biophysicist, talented and brilliant popularizer of science, whose works are readable in one go, as well as the author of unforgettable pranks and jokes. Gamow was a Fellow of the Danish Royal Academy of Sciences, the American Academy of Arts and Sciences, the International Astronomical Union, the American Physical Society, an honorary doctor of countless universities. Although his name is little known in Ukraine, the history of science would be incomplete without him. From an early age G. Gamow has shown a great interest in scientific research, using a microscope to look for erythrocytes and a telescope to observe the Halley comet. He graduated from the Faculty of Physics and Mathematics of Leningrad State University, where he followed classes of Professor O. Friedman, founder of the evolutionary cosmology. He has undergone training at the University of Goettingen, the center of theoretical physics at the time, worked for Nobel Prize winners Professors E. Rutherford and N. Bohr. At the age of 28, G. Gamow, by the recommendation of academician V. Vernadskyi, became the member of the Academy of Sciences of USSR, the youngest member in the entire history of its existence. Throughout his life, G. Gamow was interested in the fundamental scientific problems and made numerous world-class discoveries that are written by golden letters in the treasury of the human civilization. He has found explanation to the E. Rutherford’s experiments with alpha particles (tunnelling effect); introduced the empirical formula of Geiger – Nettoll, connecting the energy of alpha particles to the half-life of radioactive nuclei. G. Gamow is one of the pioneers of the liquid-drop model of a nucleus, and the application of nuclear physics to the evolution of stars. He proposed a fantastic hypothesis about the early universe, suggesting it being not only super dense but also very hot. He also built the Big Bang theory, which led to the existence of relic radiation (space microwave background) with the characteristic temperature of 5–7 degrees above the absolute zero, detected by methods of radio astronomy. He proposed a triplet model of the genetic code - the alphabet of life with three-letter words, experimentally proven by X-ray structural studies of DNA and empirically established rules of E. Chargaff. These discoveries have greatly contributed not only to the development of the modern science, but to the industrial and economic expansion of humanity.